PENERAPAN STEAM BERBASIS PROYEK UNTUK MELATIH KREATIVITAS DAN KOLABORASI SISWA KELAS 3 PADA MATERI KLASIFIKASI HEWAN MELALUI GAME EDUKATIF - Dwi Andini; Aisyah Amini Hendarsih; Alya Syifa Devany; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the need for science learning on animal classification materials that can improve conceptual understanding, creativity, and collaboration among elementary school students. The purpose of this study was to determine the effect of implementing project-based learning with a STEAM approach through educational games on the learning outcomes of third-grade students at SDN 42 Pekanbaru. This study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design involving 33 students. The implementation was conducted in two meetings, consisting of pretest administration, material delivery using the Cambridge module, group formation, implementation of an educational game project entitled Discover Animal Classification, and posttest administration. Data were collected through learning outcome tests and analyzed descriptively and inferentially. The results showed that project-based learning with a STEAM approach through educational games was able to improve students’ understanding in distinguishing vertebrate and invertebrate animals, classifying animals based on their diets, and identifying their locomotor organs. In addition, students became more active, enthusiastic, creative, and able to collaborate effectively in groups. Therefore, this learning model is effective in improving learning outcomes and developing 21st-century skills among elementary school students.